Coronavirus (COVID-19) Impacts on Malaysian Fisheries Sectors: Lesson Learned from the Movement Control Order (MCO) - Ameer Farhan Mohd Arzaman; Hayatul Safrah Salleh; Abdul Mutalib Embong; Kais Amir Kadhim; Norzamziah Afzainizam; Loi Hoang Huy Phuoc Pham; Nurul Ashikin Abdul-Kadir; Nur Yuhanis Mohd Nasir (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The COVID-19 pandemic has caused an increase in the price of marine resources and the income of coastal communities has been affected. The government and the authorities need to come out with several incentives to control this condition and the request for fish markets can be met customarily without rising prices and declining marine resources. Malaysian Fisheries Development Authority (LKIM) a body that has a direct link to the fishing industry needs to ensure that all fishermen's associations participate in the purchase and marketing of fishermen's catch. Adaptation of fish producers will pave the way for all coastal communities to develop more organized fishing systems and sufficient food sources Abstract COVID-19 has a significant impact on the fishery industry, economy, and food supply. The government of Malaysia imposes a Movement Control Order (MCO) to curb the spread of COVID-19 infection. Although the MCO implementation has benefits in terms of public health, it has affected the fishery industry and the livelihood of coastal communities in Malaysia. This study aimed to identify the impact of the COVID-19 pandemic on the fishery industry and their livelihoods during that period of calamity. Qualitative research and thematic analysis were employed to seek deeper information on the real situation that retards the fishing activities to the opt stage. COVID-19 has already revealed gaps in health care, the economy, and food systems. The findings obtained can provide recommendations to the government to provide initiatives to fishermen to help them maintain and improve their livelihood. However, this study has limitations as the number of respondents is relatively small due to the restrictions of movement allowed by the government. Future studies could be further enhanced in terms of the impact of COVID-19 after movement restrictions have been loosened and could use a quantitative approach to obtain significant data.